HUBUNGAN EKSPEKTASI USAHA DAN EKSPETASI KERJA DENGAN PEMANFAATAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DI RUMAH SAKIT UMUM SEMBIRING KABUPATEN DELI SERDANG TAHUN 2021 - Redyanto Sidi; Raskita Irena Debora Tarigan; Dessy Listiawaty; Derri Afrian; Hetty Okamona (Jurnal Penelitian Kesmasy, 2021)
Hospitals are required to have a SIMRS that functions according to Law of the Republic of Indonesia Number 44 of 2009 concerning raft houses. However, based on data from the Ministry of Health in 2019 out of 2,761 hospitals in Indonesia, only 1,564 hospitals (56%) use SIMRS and function. The purpose of this study was to analyze the factors associated with the use of SIMRS in Sembiring General Hospital using a cross sectional research design. Total population of 258 people, with a total sample of 72 health workers using a proportional stratified random sampling method. The research instrument is a questionnaire. Data analysis methods are univariate, bivariate with chi square test and multivariate with multiple linear regression tests. The results showed that of 72 health workers as many as 47 people (65%) stated that the use of SIMRS was in the good category and 35 people (35%) stated that the utilization of SIMRS was in the poor category. The results of the bivariate analysis address effort expectations, performance expectations related to the use of SIMRS with a value of p <0.05. The results of multivariate analysis showed that efforts expectations were the factors most related to the use of SIMRS with a coefficient value (0.012). It is recommended that hospitals provide SIMRS that is easy to operate, in order to improve the performance of health workers with the influence of a good social environment and the conditions of the supporting facilities.